Estimating the Present Value of Carbon Sequestration in U.S. Forests, 2015–2050, for Evaluating Federal Climate Change Mitigation Policies. (April 2020) - Haight, Robert G.; Bluffstone, Randall; Kline, Jeffrey D.; Coulston, John W.; Wear, David N.; Zook, Kate
Abstract: We demonstrate an application evaluating carbon sequestration benefits from federal policy alternatives. Using detailed forest inventory data, we projected carbon sequestration outcomes in the coterminous 48 states for a baseline scenario and three policy scenarios through 2050. Alternatives included (1) reducing deforestation from development, (2) afforestation in the eastern United States and reforestation in the western United States, and (3) reducing stand-replacing wildfires. We used social cost of carbon estimates to evaluate the present value of carbon sequestration benefits gained with each policy. Results suggest that afforestation and reforestation would provide the greatest marginal increase in carbon benefit, far exceeding policy cost.